The Use of Biochar From Cow Feces and Bioboost in The Red Chili Plant (Capsicum annum L.) - Dewiyati Susanti Dapa; Yohanes Parlindungan Situmeang; Ketut Agung Sudewa (SEAS (Sustainable Environment Agricultural Science), 2019)
The purpose of this research is to know the influence and interaction by giving biochar and bioboost of the growth and fruitage of chili. This research is used Randomized Block Design factorial patterned with 2 factor, the first treatment is biochar of cow feces with 4 standards of dosage (0; 5; 10; dan 15 ton ha-1), meanwhile the second factor is bioboost with 3 standards of dosage (30, 60, dan 90 cc tan-1). The interaction between biochar and bioboost gave the real influenced into the height, weight of fresh roots, oven-dry of the leaves, oven-dry of the chili each plant but gave not real influenced into the other variables. The height weight of dry chili was obtained into the interaction between biochar 10 ton ha-1 and 60 cc tan-1 is 3.20 g or increased by 28 % if compared with the lowest weight in bioboost 60 cc tan-1 without biochar is 2.25 g.